2007
DOI: 10.1111/j.1365-2648.2007.04216.x
|View full text |Cite
|
Sign up to set email alerts
|

A socially inclusive approach to user participation in higher education

Abstract: The search for an optimum model of involvement may prove elusive, but the need to research and debate different strategies, to avoid tokenism and exploitation, remains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
95
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(97 citation statements)
references
References 27 publications
2
95
0
Order By: Relevance
“…A follow up to paper 29, published after the cut-off date (Simons et al 2007) reported that the post was not well integrated in the team in terms of normal educational activities and processes. Some of the educators demonstrated resistance to the post and it was concluded that strategies to avoid stigmatisation and discrimination were not always effective.…”
Section: Discussionmentioning
confidence: 99%
“…A follow up to paper 29, published after the cut-off date (Simons et al 2007) reported that the post was not well integrated in the team in terms of normal educational activities and processes. Some of the educators demonstrated resistance to the post and it was concluded that strategies to avoid stigmatisation and discrimination were not always effective.…”
Section: Discussionmentioning
confidence: 99%
“…Happelle ta la nd Khoo et al found that therew as an impacto np ractice with severalo fthe postgraduates in theirevaluation havingintroduceduserfocused initiativesin practice.O thers, such as Simons et al (2006),d rawattention to the work that stillh as to be done to achieveasociallyi nclusive approacht os ervice user involvement in higher education. Organisationalf actorsa nd unintentional discrimination mayintroduceb arrierst o participation e.g.…”
mentioning
confidence: 99%
“…We recognise that terms such as service user, patient, carer or experts by experience will include people who are also students; practitioners, academics and professionals; people of many skills and backgrounds and multiple roles and identities. We seek to involve a wide range of people in many different ways, to reflect this diversity and to address the need identified in the literature to involve seldom heard voices (Duffy, 2013) and to explore different models and strategies to avoid tokenism (Simons, Tee, Lathlean, Burgess, Herbert and Gibson, 2007). The types of involvement which students and graduates were asked to reflect on in this study therefore were diverse.…”
Section: Contextmentioning
confidence: 99%